TANTANGAN DAN PELUANG EDUPRENEURSHIP : KAJIAN LITERATUR DI ERA DIGITAL - Rada Anjelina; Fita Azzahra (CV. Denasya Smart Publisher, 2025)
Edupreneurship, as a bridge between education and business, has emerged as an important topic in the digital era. The purpose of this research is to analyze the challenges and opportunities presented by entrepreneurship through a literature study. The challenges identified are fierce competition, digital access gaps, and the growing need for innovation. In addition, there has been a significant increase in the use of technology, such as online learning, digital platforms, and access to world markets. This study emphasizes the importance of creativity, capital investment, and technological adaptation in fostering entrepreneurship in the digital age.